Editorial: tripartite motif 26 inhibits hepatitis B virus replication and its genetic polymorphism predicts response to interferon treatment—towards a better understanding of interferon responsiveness in chronic hepatitis B. Authors' reply. Issue 6 (22nd August 2022) - Luo, Mengqi; Jiang, De‐Ke
Abstract : LINKED CONTENT This article is linked to Luo et al papers. To view these articles, visit https://doi.org/10.1111/apt.17124 and https://doi.org/10.1111/apt.17159